2017
DOI: 10.1017/s0007485317000050
|View full text |Cite
|
Sign up to set email alerts
|

Deterrent activity of hops flavonoids and their derivatives against stored product pests

Abstract: Five flavonoids from hops, two of their derivatives, along with naringenin used as a model compound, were tested for their antifeedant activity against three coleopteran stored product pests: Sitophilus granarius L., Tribolium confusum Duv. and Trogoderma granarium Everts. The introduction, into the tested flavonoid molecules, of additional structural fragments such as prenyl or dimethylpyran moiety, is proposed to significantly alter the deterrent activity of the compounds. The prenyl moiety in flavonoids inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Given the likely role of hop leaf gland contents at deterring insect herbivores and the apparent heritability of gland density, breeders may want to consider H. neomexicanus for natural, antifeedant traits. ,,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the likely role of hop leaf gland contents at deterring insect herbivores and the apparent heritability of gland density, breeders may want to consider H. neomexicanus for natural, antifeedant traits. ,,, …”
Section: Resultsmentioning
confidence: 99%
“…One aspect of biological diversity is phytochemical diversity. The significance of hop phytochemical constituents for brewing, medicine, and agronomic traits is documented. While many phytochemical studies on wild hop have focused on the cones, understanding hop leaf phytochemistry is also important for a few reasons. First, leaf chemistry affects agronomic traits such as disease and pest resistance. , Second, unlike cones, leaves are available throughout most developmental stages and are found on both male and female plants.…”
Section: Introductionmentioning
confidence: 99%
“…Lane et al [26] found that isoflavonoids from root of Lupinus angustifolius showed high feeding-deterrent activity associated with high antifungal activity. Jackowski et al [27] tested hops flavonoids’ deterrent activity against stored product pests, and the results showed that the pests responded to the tested compounds with considerable reduction of its feeding activity. These results coincide with ours, in that the insect feeding rate of red pods was significantly lowered.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was also noticed that the activity of the hop extract was stronger than that of pure XN. Changes in the chemical structure of XN by cyclization, isomerization, oxidation, and reduction increased feeding deterrence (Jackowski et al., ). Isoxanthohumol (IXN) showed good deterrent activity ( T ‐value = 103.4) for S. granarius adults, which was 13.4 points higher than that of XN; the T ‐value of xanthohumol flavone (FXN) was 22.9 points higher and that of α,β‐dihydroxanthohumol was 22 points higher than the T ‐value of XN.…”
Section: Plant‐derived Substances Against Beetle Pests Of Stored Foodmentioning
confidence: 99%